Shallow geothermal heat in Western Canada: climatic warming impact changes with time– depth - Majorowicz, Jacek; Šafanda, Jan (Bulletin of Geography. Physical Geography Series, 2023)
Gain of heat and temperature in the shallow subsurface over the last decades/century has been impacted by the industrial period climatic surface air temperature (SAT) increase. Detailed study of the available temperature-depth data based on 43 wells with single and repeated temperature logs done by the first author has been combined with data base information (Jessop et al 2005) to create temperature maps at depth. Based on these 43 logs it is shown that the heat flux increases with depth in most cases for the available depth data range from surface to some 200m. Model of heat flow versus depth based on the surface air temperature changes through the industrial epoque climatic warming explains the data. Spatial and depth distribution of available temperature and heat gain through the provinces of the Western Canadian Sedimentary Basin WCSB shows that drilling closer to surface is more economic than deeper to 50-100m.